Pyrethrum and its Future in India - Shetty, K. A. Bhoja (Indian Forester, 1953)
Pyrethrum growing on a commercial scale was first taken up in India during the Second World War due to the cessation of supplies from Japan and diminution in the import from Kenya. Subsequently, pyrethrum cultivation in the country was more or less given up completely due to the discovery of synthetic insecticides such as D.D.T. and Gammexane which were considered to be more efficient. Besides the past attempts at the cultivation of pyrethrum were by no means a success in this country, the yields being abnormally low. But very soon it was revealed that the synthetic insecticides like D.D. T. and Gammexane had very many drawbacks and that it is inadvisable to use them indiscriminately. In the light of these findings the importance of pyrethrum again emerged out. The past attempts at the growing of pyrethrum in India are briefly outlined and the methods of pyrethrum culture in other countries like Japan and Kenya have also been indicated in this article. The necessity for delineating the optimum zones for pyrethrum cultivation and determining the most suitable method of propagation by a co-ordinated scheme of research has been stressed. The future prospects are bright for the crop in India, given a plan for rational extension under a co-ordinated scheme of research and extension.